Effects of drought stress on the growth, yield and physiological traits of Thai Super Sweet Corn - Evelyn Koay Shin Rou; Alissa Nabilla Zamri; Lum Mok Sam (Malaysian Society of Plant Physiology, 2020)
Growth and yield performances of Thai Super Sweet (TSS) corn cultivar treated with various drought stress levels (25%, 50% and 100% Field Capacity, FC) at various growth stages (vegetative, pre-flowering and flowering) were investigated in an insect-proof net-house of Faculty of Sustainable Agriculture, Universiti Malaysia Sabah, Sandakan Campus. Drought treatments were applied at vegetative (14 to 34 days after sowing (DAS)), pre-flowering (35 to 55 DAS) and flowering (48 to 68 DAS) stages. Parameters measured and statistically analysed were growth, chlorophyll content, proline content and yield. The experiment was conducted as 3 x 3 factorial arrangements of treatments with a completely randomised design with four replications for each treatment. Length of first cob and fresh weight of the first cob showed interaction effects among the drought and growth stage treatments while chlorophyll content, number of cobs, cob girth, number of grains, 100 grains weight and proline content showed significant effects among drought levels treatments and cob girth showed significant effect among growth stages. Shorter flowering time (tasseling at 42 DAS) was found on drought treatment of 25% FC at the pre-flowering stage. It can be concluded that vegetative and flowering stages were sensitive to drought compared to the pre-flowering stage, where the yield components of vegetative and flowering stages were lower compared to the preflowering stage. During the pre-flowering drought period, TSS expressed tolerance response through the higher levels of chlorophyll and proline contents and hence was able to perform the best overall yield components